2001
DOI: 10.1007/s004180100298
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine expression in rat molar gingival periodontal tissues after topical application of lipopolysaccharide

Abstract: It is well known that proinflammatory cytokines produced by host cells play an important role in periodontal tissue destruction. However, the localization of the cytokines in in vivo periodontal tissues during development of periodontal disease has not been determined. Immunohistochemical expression of proinflammatory cytokines including IL-1α, IL-1β, and TNF-α was examined at 1 and 3 h, and 1, 2, 3, and 7 days after topical application of lipopolysaccharide (LPS; 5 mg/ml in physiological saline) from E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 26 publications
6
31
0
1
Order By: Relevance
“…It was clearly demonstrated that the gingival epithelium was constitutively stained for both IL-1a and TNF-a. This observation is in agreement with previous data (15,22,31) and implies some degree of inflammation in the rat gingiva under normal conditions. When orthodontic forces were applied, there was not only increased gingival staining reaction for the above cytokines, but also extension of the staining in the subjunctional area, including the PDL and the alveolar bone below the gingiva, indicating a substantial inflammatory reaction over a greater area.…”
Section: Discussionsupporting
confidence: 93%
“…It was clearly demonstrated that the gingival epithelium was constitutively stained for both IL-1a and TNF-a. This observation is in agreement with previous data (15,22,31) and implies some degree of inflammation in the rat gingiva under normal conditions. When orthodontic forces were applied, there was not only increased gingival staining reaction for the above cytokines, but also extension of the staining in the subjunctional area, including the PDL and the alveolar bone below the gingiva, indicating a substantial inflammatory reaction over a greater area.…”
Section: Discussionsupporting
confidence: 93%
“…For this purpose, the levels of TNFα and IL-4 were analyzed in which TNFα:IL-4 ratio was used as predictor of inflammation (Tsurumi, Que, Ryan, Tompkins, & Rahme, 2016). The results showed that incubation of human PDLCs with LPS resulted in higher TNFα release, which corroborated with data from previous studies (Miyauchi et al, 2001;Morsczeck, Dress, & Gosau, 2012;Yamaji et al, 1995;Yoshimura et al, 1987).…”
Section: Discussionsupporting
confidence: 81%
“…This is also reflected by receptor distribution, as monocytes have relatively abundant p55 and p75 TNF receptors (8). In a study on cytokine expression in rat molar periodontal tissues after local application of inflammation-challenging lipopolysaccharide, Miyauchi et al (44) found TNFa expression in macrophages, as well as in preosteoclasts and osteoclasts on the alveolar bone surface. Another reason for the different potencies between the blocking of IL-1 and TNFa may lie in a possible agonistic activity of soluble IL-1 receptors by which compensatory events could be induced.…”
Section: Discussionmentioning
confidence: 99%